2024
DOI: 10.1186/s40635-024-00600-3
|View full text |Cite
|
Sign up to set email alerts
|

HS-GC–MS analysis of volatile organic compounds after hyperoxia-induced oxidative stress: a validation study

Thijs A. Lilien,
Dominic W. Fenn,
Paul Brinkman
et al.

Abstract: Background Exhaled volatile organic compounds (VOCs), particularly hydrocarbons from oxidative stress-induced lipid peroxidation, are associated with hyperoxia exposure. However, important heterogeneity amongst identified VOCs and concerns about their precise pathophysiological origins warrant translational studies assessing their validity as a marker of hyperoxia-induced oxidative stress. Therefore, this study sought to examine changes in VOCs previously associated with the oxidative stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…Although both compounds were detected in our study, no significant differences in signal intensities were noted between the intervention and control groups. The other study also reported a decrease in decane, mirroring our findings [30].…”
Section: Identified Compounds and Signal Intensitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Although both compounds were detected in our study, no significant differences in signal intensities were noted between the intervention and control groups. The other study also reported a decrease in decane, mirroring our findings [30].…”
Section: Identified Compounds and Signal Intensitiessupporting
confidence: 90%
“…Nevertheless, the signal strengths of all molecules were higher in the control group than in the intervention group. This observation is consistent with findings from two separate studies that subjected similar lung epithelial cells to hydrogen peroxide (H 2 O 2 ) or oxygen concentrations exceeding 90% for a duration of 24 h, inducing substantial oxidative stress [2,30]. In one study, the intervention group showed reduced octane levels compared to the control group, while 2-ethyl-1-hexanol exhibited heightened signal intensity [2].…”
Section: Identified Compounds and Signal Intensitiessupporting
confidence: 86%